İsmail Gaspralı’s Letters to Alexey Suvorin (1876) and Pavel Vyazemski (1882) - Ilya Zaytsev (Крымское историческое обозрение)
The Paper is a Publication of Two unknown Letters by İsmail Gaspralı to Alexey Suvorin (1876) and Pavel Vyazemski (1882)